Pengaruh Pembelajaran Daring Media Whatsapp Group Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran PAI (Era Revolusi 4.0) di SMP Muhammadiyah Palangka Raya - Dewi Pratiwi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This study aims to determine the effect of online learning on student learning motivation in PAI subjects in the revolutionary era 4.0. The industrial revolution 4.0 is often referred to as a cyber physical system. This revolution focuses on automation and collaboration with cyber technology. The main characteristic of this industrial revolution is the incorporation of information and communication technology in the industrial sector. The emergence of the industrial revolution caused changes in various sectors. If previously it required quite a lot of workers, now everything can be replaced with the use of technological machines. The method in this study is to use the ex post facto method. The sampling technique in this study was using a proportional stratified random sampling technique. The instrument in this study used a closed questionnaire in the form of a Likert scale and documentation. The data analysis technique used in this study is product moment correlation, Spearman rank correlation, and the coefficient of determination. The result of this calculation is the SPSS 25 program. Based on the results of the research, it shows that from the calculation data, it is concluded that: (1) Online learning of students with an average value of 3.358 is included in the high category. (2) Student motivation with an average score of 3.790 in the high category (3) There is an influence between online learning and student motivation. This is evident from the test of the coefficient of determination which is 11.8% which states that Ho is rejected and Ha is accepted Keywords: Online Learning, Islamic Religious Education Learning Motivation, Revolutionary Era 4.0